Structural transformations and stability of benzo[a]pyrene under high pressure - Wenju Zhou; Andrey Aslandukov; Anastasiia Minchenkova; Michael Hanfland; Leonid Dubrovinsky; Natalia Dubrovinskaia (IUCrJ)
Benzo[a]pyrene (BaP), C20H12, is a representative of polycyclic aromatic hydrocarbons (PAHs), which are ubiquitous in nature and the universe, where they are subjected to extreme conditions. This paper reports the results of investigations of the high-pressure behavior of BaP up to 28 GPa using in situ synchrotron single-crystal X-ray diffraction. We identified two previously unknown polymorphs, BaP-II (P21/c) at 4.8 GPa and BaP-III (P1) at 7.1 GPa. The structural transformation from BaP-I (P21/c) to BaP-II (P21/c) manifests as an abrupt change in the intermolecular angle and the unit-cell parameters a and b, whereas the transformation from BaP-II (P21/c) to BaP-III (P1) is characterized by a decrease in symmetry. According to density functional theory calculations, BaP-III is the most stable phase above 3.5 GPa. These studies advance our understanding of the structural dynamics and stability of PAHs under high pressure.